(untitled) (Hematology Meeting Reports, 2009)
The stomach is the commonest site of MALT-type lymphoma development, although the gastric mucosa is primarily devoid of lymphoid tissue. Helicobacter pylori leads to an active chronic gastritis and to the recruitment to of both B cells and T cells to mucosa forming mucosa-associated lymphoid tissue (MALT). In the recent decade evidence accumulated that Helicobacter pylori infection is linked to the pathogenesis of gastric MALT-type lymphoma. Antigen- with T-cell stimulation may have important impact on the initial phase of tumor development, while Helicobacter pylori eradication can result in tumor regression in most cases.